Marketing Communications as Strategy Expanding Market Share In Era 4.0 - Abdul Haris; Hasrat Effendi Samosir; Siti Hawa Lubis (Universitas Pendidikan Ganesha, 2023)
Today's markets and commercial connections span the globe. Meanwhile, the slow pace of economic growth and the resulting difficulties for businesses stimulate a drive toward greater efficiency and effectiveness. Since marketing efforts affect the present and future health of markets and businesses, they have evolved into an essential business component. Adapting to the ever-changing environment is one of the most important aspects of using them. This study identifies successful strategies in marketing communications that can be used to achieve success based on factors such as culture, lifestyle, purchasing habits, consumption patterns, preferred communication channels, and more. In this study, researchers used a qualitative technique, which involves gathering information via in-depth interviews, document analysis, and direct observation of the topic. In this context, marketing communication is crucial since it helps direct potential customers to the products they need based on their culture, lifestyle, purchasing habits, consumption patterns, preferred communication channels, and more. Promoting the product to address the market's requirements, desires, and expectations relies on marketing communication to disseminate information about the product. It might lead to the growth of new market segments. If a product's market share grows, so do its marketing successes.